Single-center experience in sutureless aortic valve implantation using two aortic valve prostheses - Rings, Laura; Ntinopoulos, Vasileios; Dushaj, Stak; Hoti, Gojart; Fleckenstein, Philine; Dzemali, Omer; Häussler, Achim (Journal of Cardiology and Cardiovascular Medicine, 2022)
Background and aim of the study: Sutureless aortic valves are used to reduce operation time. However, the stent implantation might cause postoperative ECG alterations and a higher risk of paravalvular leakage. In literature, some cases of thrombocytopenia are described after implantation. We investigated the Sorin Perceval S Sutureless Valve and the Edwards Intuity Sutureless Valve. Material and methods: Seventy-nine patients underwent aortic valve replacement using a sutureless valve in a single center between 2015 - 2018. Thirty-seven patients received Sorin Perceval S (Group A) and 42 Edwards Intuity (Group B). Simultaneous bypass surgery was performed in 23 patients in Group A and 22 patients in Group B. We compared the groups regarding postoperative TTE and paravalvular leakage, postoperative ECG alterations, need for pacemaker implantation, postoperative platelet count, and 30-day mortality Results: Only in Group B 2 patients had paravalvular leakage, and one was reoperated within the same hospital stay. In Group A, nine patients suffered from postoperative atrial fibrillation, and in Group B, 16 patients. Left bundle branch block (LBBB) was observed in 5 patients in Group A, and 13 patients in Group B. Two patients in Group A needed a definite pacemaker, and five patients in Group B. Tachy-Brady Syndrome and LBBB were observed more frequently in Group B as well as ECG alterations. One patient died within 30 days in Group A due to multiorgan failure. This patient was older and multimorbid compared to the average. Regarding platelet count, we saw a statistically significant decrease in both groups. There were no major bleeding complications or reoperations due to hemorrhage. Conclusion: Our data shows that sutureless aortic valve replacement is associated with new postoperative ECG alterations, which are self-limiting in most cases. Compared to the literature pacemaker implantation rate in Group B is higher.